Making miracles - Fox, Arnold; Fox, Barry (Ahemedabad : Jaico Publishing House, 2012)
PAs you follow the simple day-by-day program designed by Drs. Arnold and Barry Fox, you will learn to tap into the secrets of miracle making that are in your control. You will, discover the miraculous power of prayer, overcome life's obstacles by changing your self-talk, make sound health a daily miracle as you deal with stress, depression heart disease and cancer, learn to dispel the gloom and doom of depression for a positive mental attitude, put your faith to work for you so that you can create a life filled with miracles beginning today, incorporate this process fully into your own life so that you can begin to touch the lives of those you love.
Keywords: Cancer -- Biography. -- Patients -- United States; Miracles